Multipotentializations and Nonlocal Symmetries: Kupershmidt, Kaup-Kupershmidt and Sawada-Kotera Equations - Reyes-Garcia, E (Taylor and Francis Ltd., 2017)
In this letter we report a new invariant for the Sawada-Kotera equation that is obtained by a systematic potentialization of the Kupershmidt equation. We show that this result can be derived from nonlocal symmetries and that, conversely, a previously known invariant of the Kaup-Kupershmidt equation can be recovered using potentializations. © 2017 the authors.